A conductive WC / β-SiAlON composite ceramic tool material with high mechanical properties and a preparation method thereof

By adding WC powder to β-SiAlON ceramics and using discharge plasma sintering technology, the problem of difficult processing and insufficient conductivity of β-SiAlON ceramics is solved, and the high conductivity and mechanical properties of composite ceramic materials are achieved, which is suitable for applications such as high-efficiency cutting.

CN118993742BActive Publication Date: 2025-03-21NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411111393.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2025-03-21
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively process the hard ceramic material β-SiAlON, and its conductivity is insufficient, limiting its wide application in applications such as efficient cutting.

Method used

By adding WC powder as the conductive phase and using discharge plasma sintering technology, β-SiAlON ceramics have conductive properties while achieving toughening and strengthening effects.

Benefits of technology

It has achieved good conductivity and high mechanical properties of WC/β-SiAlON composite ceramic materials, reduced resistivity, significantly improved Vickers hardness and fracture toughness, and is suitable for applications such as high-efficiency cutting tools.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118993742B_ABST
    Figure CN118993742B_ABST
Patent Text Reader

Abstract

The present invention discloses a high mechanical property conductive WC / β-SiAlON composite ceramic tool material and a preparation method thereof, and belongs to the technical field of ceramic material preparation. The high mechanical property conductive WC / β-SiAlON composite ceramic tool material of the present invention, in terms of volume percentage, comprises raw materials including: 70-80% β-SiAlON ceramic powder and 20-30% WC powder. The WC / β-SiAlON composite ceramic tool material of the present invention has good electrical conductivity and high mechanical properties, with its resistivity being reduced to 0.64Ω·m, its Vickers hardness being up to 17.23±0.29GPa, and its fracture toughness being up to 7.09±0.14MPa·m 1 / 2 Compared with pure β-SiAlON ceramics without the addition of a second phase, the resistivity decreases by about 10 10 times, the Vickers hardness increased by 4.68%, and the fracture toughness increased by 4.11%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic material preparation, in particular to a high-mechanical-property conductive WC / β-SiAlON composite ceramic tool material and a preparation method thereof. Background Art

[0002] β-SiAlON ceramics are a solid solution formed by dissolving Al2O3 into Si3N4. They possess excellent mechanical properties and high-temperature stability, making them a highly promising high-temperature engineering material widely used in the production of cutting tools, high-performance bearings, and high-temperature refractories. However, β-SiAlON ceramics are extremely hard and difficult to machine. Currently, they can only be processed using traditional processes such as diamond wire saws, diamond slicing, and grinding, resulting in low processing efficiency. If conductive β-SiAlON ceramics could be prepared and processed through electrospark machining, this would greatly improve production efficiency and benefits, and further expand the application range of β-SiAlON ceramics (such as in extreme applications such as high-speed cutting). Therefore, the development of a conductive β-SiAlON ceramic material with high mechanical properties is highly desirable.

[0003] However, there is currently little research on the conductivity of β-SiAlON ceramics, and its ever-expanding application needs have intensified the necessity of development and research in this area. Toughening and reinforcing β-SiAlON ceramics is also an important part of promoting β-SiAlON ceramics. Summary of the Invention

[0004] The present invention aims to provide a conductive WC / β-SiAlON composite ceramic tool material with high mechanical properties and a method for its preparation to address the aforementioned problems of the prior art. By adding WC as a conductive phase and employing spark plasma sintering, the present invention imparts conductivity to the β-SiAlON ceramic while also providing toughness and reinforcement.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is a high mechanical property conductive WC / β-SiAlON composite ceramic tool material, the raw materials of which include, by volume percentage, 70-80% β-SiAlON ceramic powder and 20-30% WC powder (conductive phase WC powder).

[0007] Preferably, the raw materials of the β-SiAlON ceramic powder include, by mass percentage, 84-85% Si3N4 powder, 5-6% Al2O3 powder, 2-3% AlN powder and 6-9% Sm2O3 powder.

[0008] More preferably, the raw materials of the β-SiAlON ceramic powder include, by mass percentage, 84.18% Si3N4 powder, 5.58% Al2O3 powder, 2.24% AlN powder and 8% Sm2O3 powder; the solid solution parameter z value of β-SiAlON in the β-SiAlON ceramic powder is 0.5.

[0009] Preferably, the method for preparing the β-SiAlON ceramic powder comprises the following steps:

[0010] The raw materials are mixed in an organic solvent, subjected to ultrasonic oscillation and mechanical stirring, and then dried, ground and sieved to obtain the β-SiAlON ceramic powder.

[0011] Preferably, the particle size of the WC powder is 0.05-1 μm, more preferably 0.06 μm.

[0012] Technical solution 2 of the present invention: A method for preparing the above-mentioned WC / β-SiAlON composite ceramic tool material comprises the following steps:

[0013] (1) adding the raw materials into an organic solvent, ultrasonically vibrating and mechanically stirring, drying, grinding and sieving to obtain a WC / β-SiAlON composite ceramic raw powder;

[0014] (2) The WC / β-SiAlON composite ceramic raw powder is sintered to obtain the WC / β-SiAlON composite ceramic tool material.

[0015] Preferably, in step (1), the mass ratio of the raw material to the organic solvent is 1:(2-5), more preferably 1:3; the frequency of the ultrasonic oscillation is 30-50 kHz, more preferably 40 kHz; the time of the ultrasonic oscillation plus mechanical stirring is 0.5-3 h, more preferably 2 h.

[0016] Preferably, in step (1), the drying temperature is 90-150° C., more preferably 120° C.; the drying time is 5-7 h, more preferably 6 h.

[0017] Preferably, in step (1), the mesh size of the sieving is 100 to 300 meshes, more preferably 100 meshes.

[0018] Preferably, in step (2), the sintering is spark plasma sintering;

[0019] The process parameters of the spark plasma sintering include: a sintering pressure of 20 to 50 MPa, a sintering temperature of 1650 to 1750° C., and a holding time of 5 to 15 minutes.

[0020] More preferably, in step (2), the process parameters of the spark plasma sintering include: sintering pressure of 30 MPa, sintering temperature of 1700° C., and holding time of 10 min.

[0021] The third technical solution of the present invention: an application of the above-mentioned WC / β-SiAlON composite ceramic tool material in the preparation of cutting tools.

[0022] The present invention discloses the following technical effects:

[0023] (1) The WC / β-SiAlON composite ceramic tool material of the present invention has good electrical conductivity and high mechanical properties. Its resistivity can be reduced to 0.64Ω·m, its Vickers hardness can reach 17.23±0.29GPa, and its fracture toughness can reach 7.09±0.14MPa·m 1 / 2 Compared with pure β-SiAlON ceramics without the addition of the second phase, the resistivity is reduced by about 10 10 times, the Vickers hardness increased by 4.68%, and the fracture toughness increased by 4.11%.

[0024] (2) The present invention uses β-SiAlON ceramic as a matrix, and adopts Si3N4, Al2O3, AlN and Sm2O3 powders as the initial raw materials of β-SiAlON ceramic, among which Sm2O3 is used as a sintering aid for sintering β-SiAlON ceramic, and metal carbide WC powder (WC powder has good electrical conductivity and high mechanical properties, which enables β-SiAlON ceramic to achieve electrical conductivity and toughening effect) is selected as the conductive phase. After all raw materials (β-SiAlON ceramic powder and WC powder) are uniformly mixed, spark plasma sintering technology is used to prepare WC / β-SiAlON composite ceramic tool material, which has both excellent electrical conductivity and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 This is an SEM image of the polished surface of the WC / β-SiAlON composite ceramic tool material prepared in Example 1 of the present invention;

[0027] Figure 2 This is an SEM image of the polished surface of the WC / β-SiAlON composite ceramic tool material prepared in Example 2 of the present invention;

[0028] Figure 3 This is an SEM image of the polished surface of the WC / β-SiAlON composite ceramic tool material prepared in Comparative Example 1 of the present invention;

[0029] Figure 4 These are the XRD patterns of the WC / β-SiAlON composite ceramic tool materials prepared in Examples 1-2 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0030] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0031] It should be understood that the terms described herein are intended only to describe particular embodiments and are not intended to limit the present invention. In addition, for numerical ranges herein, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between any intermediate value within a stated value or stated range and any other stated value or intermediate value within the stated range is also encompassed by the present invention. The upper and lower limits of these smaller ranges may be independently included or excluded within the scope.

[0032] Unless otherwise indicated, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of any conflict with any incorporated document, the contents of this specification shall prevail.

[0033] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments described herein without departing from the scope or spirit of the invention. Other embodiments will be apparent to those skilled in the art from the description of the invention. The description and examples are intended to be exemplary only.

[0034] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0035] In a first aspect, the present invention provides a conductive WC / β-SiAlON composite ceramic tool material with high mechanical properties. The raw materials include, by volume percentage, 70-80% β-SiAlON ceramic powder and 20-30% WC powder (conductive phase WC powder).

[0036] Preferably, the raw materials of the β-SiAlON ceramic powder include, by mass percentage, 84-85% Si3N4 powder, 5-6% Al2O3 powder, 2-3% AlN powder and 6-9% Sm2O3 powder.

[0037] More preferably, the β-SiAlON ceramic powder comprises, by mass percentage, 84.18% Si3N4 powder, 5.58% Al2O3 powder, 2.24% AlN powder and 8% Sm2O3 powder; the solid solution parameter z value of β-SiAlON in the β-SiAlON ceramic powder is 0.5.

[0038] The β-SiAlON ceramics sintered at this ratio have better performance, paving the way for further toughening.

[0039] Preferably, the method for preparing β-SiAlON ceramic powder comprises the following steps:

[0040] The raw materials are mixed in an organic solvent, subjected to ultrasonic oscillation and mechanical stirring for 2 hours, and then dried (dried at 120° C. for 6 hours), ground and sieved to obtain β-SiAlON ceramic powder.

[0041] Preferably, the particle size of the WC powder is 0.05 to 1 μm, more preferably 0.06 μm.

[0042] In a second aspect, the present invention provides a method for preparing the above-mentioned WC / β-SiAlON composite ceramic tool material, comprising the following steps:

[0043] (1) adding the raw materials into an organic solvent, ultrasonically vibrating and mechanically stirring, drying, grinding and sieving to obtain a WC / β-SiAlON composite ceramic raw powder;

[0044] (2) The WC / β-SiAlON composite ceramic raw powder is sintered to obtain the WC / β-SiAlON composite ceramic tool material.

[0045] Preferably, in step (1), the mass ratio of the raw material to the organic solvent is 1:(2-5), more preferably 1:3; the frequency of ultrasonic oscillation is 30-50 kHz, more preferably 40 kHz; and the time of ultrasonic oscillation plus mechanical stirring is 0.5-3 h, more preferably 2 h.

[0046] Preferably, in step (1), the drying temperature is 90-150° C., more preferably 120° C.; and the drying time is 5-7 h, more preferably 6 h.

[0047] Preferably, in step (1), the mesh size of the sieve is 100 to 300 meshes, more preferably 100 meshes.

[0048] Preferably, in step (2), the sintering is spark plasma sintering;

[0049] The process parameters of spark plasma sintering include: sintering pressure of 20 to 50 MPa, sintering temperature of 1650 to 1750° C., and holding time of 5 to 15 minutes.

[0050] More preferably, in step (2), the process parameters of spark plasma sintering include: sintering pressure of 30 MPa, sintering temperature of 1700° C., and holding time of 10 min.

[0051] The WC / β-SiAlON composite ceramic tool material prepared by the above method has a low resistivity, and under the joint action of WC and β-SiAlON grains, the mechanical properties of the WC / β-SiAlON composite ceramic material are significantly improved.

[0052] In a third aspect, the present invention provides a use of the WC / β-SiAlON composite ceramic tool material in the preparation of cutting tools.

[0053] Example 1

[0054] A preparation method of a conductive WC / β-SiAlON composite ceramic tool material with high mechanical properties:

[0055] (1) β-SiAlON ceramic powder, the raw materials include, by mass percentage, 84.18% of Si3N4 powder, 5.58% of Al2O3 powder, 2.24% of AlN powder and 8% of Sm2O3 powder.

[0056] Preparation of β-SiAlON ceramic powder: The raw materials were mixed in anhydrous ethanol according to mass percentage, subjected to ultrasonic oscillation (frequency of 40 kHz) and mechanical stirring for 2 hours, and then dried (dried at 120°C for 6 hours), ground and sieved (100 mesh) to obtain β-SiAlON ceramic powder. The solid solution parameter z value of β-SiAlON in the β-SiAlON ceramic powder was 0.5.

[0057] (2) WC / β-SiAlON composite ceramic tool material, calculated by volume percentage, the raw materials include: 80% β-SiAlON ceramic powder and 20% WC powder (particle size of 0.06 μm).

[0058] (3) The raw materials and anhydrous ethanol were mixed in a mass ratio of 1:3 by volume, and then ultrasonically oscillated at a frequency of 40 kHz and mechanically stirred for 2 h. The fully mixed slurry was then dried at 120 °C for 6 h. Finally, the dried and ground powder was sieved with a 100-mesh sieve to obtain the WC / β-SiAlON composite ceramic raw powder.

[0059] (4) The WC / β-SiAlON composite ceramic raw powder was poured into a graphite mold and then subjected to spark plasma sintering at a sintering pressure of 30 MPa. The powder was heated to 1700°C at a heating rate of 100°C / min and kept warm for 10 min. Finally, the power was turned off and cooled, and the sintered sample was demolded to obtain a WC / β-SiAlON composite ceramic tool material.

[0060] The WC / β-SiAlON composite ceramic tool material prepared in this example was subjected to an indentation test to calculate the Vickers hardness and fracture toughness. A diamond indenter was used to indent a crack at a load of 98 N for 15 seconds. The Vickers hardness (HV10) was calculated by measuring the length of the diamond diagonal in the indentation. The calculation formula is as follows:

[0061] HV=0.47P / a 2 (1)

[0062] In formula (1), HV is the Vickers hardness value of the sample, P is the indentation load, and a is half the length of the diagonal line of the diamond in the indentation.

[0063] The fracture toughness is calculated based on the crack length extending around the diamond, and the calculation formula is as follows:

[0064] K IC =0.018HV×a 0.5 (E / HV) 0.4 ×(c / a-1) -0.5 (2)

[0065] In formula (2), K IC is the fracture toughness of the sample, E is the elastic modulus of the sample (320 GPa), c is half the crack length, and HV and a are as described in formula (1).

[0066] The WC / β-SiAlON composite ceramic tool material prepared in this embodiment was subjected to microstructure scanning electron microscopy analysis, and the results are shown in FIG. Figure 1 (SEM image of polished surface).

[0067] The test results show that the WC / β-SiAlON composite ceramic tool material prepared in this embodiment has a resistivity of 0.64Ω·m, a Vickers hardness of 17.23±0.29GPa, and a fracture toughness of 7.09±0.14MPa·m. 1 / 2 .

[0068] Example 2

[0069] The same as Example 1, except that step (2) is specifically as follows: WC / β-SiAlON composite ceramic tool material, in terms of volume percentage, the raw materials include: 70% β-SiAlON ceramic powder and 30% WC powder (particle size of 0.06μm).

[0070] The WC / β-SiAlON composite ceramic tool material prepared in this embodiment was subjected to microstructure scanning electron microscopy analysis, and the results are shown in FIG. Figure 2 (SEM image of polished surface).

[0071] The test results show that the WC / β-SiAlON composite ceramic tool material prepared in this embodiment has a resistivity of 0.31Ω·m, a Vickers hardness of 17.91±0.39GPa, and a fracture toughness of 6.77±0.19MPa·m. 1 / 2 .

[0072] Comparative Example 1

[0073] The same as Example 1, except that step (2) is specifically as follows: WC / β-SiAlON composite ceramic tool material, in terms of volume percentage, the raw materials include: 90% β-SiAlON ceramic powder and 10% WC powder (particle size of 0.06μm).

[0074] The WC / β-SiAlON composite ceramic tool material prepared in this comparative example was subjected to microstructure scanning electron microscopy analysis, and the results are shown in FIG. Figure 3 (SEM image of polished surface).

[0075] The test results show that the resistivity of the WC / β-SiAlON composite ceramic tool material prepared in this comparative example is 2.01×10 9 Ω·m, Vickers hardness is 16.60±0.33GPa, fracture toughness is 6.92±0.20MPa·m 1 / 2 .

[0076] By analyzing and comparing Examples 1 to 2 and Comparative Example 1, it can be seen that the increase in WC content can dramatically reduce the resistivity of β-SiAlON ceramics. At the same time, due to the high hardness and fracture toughness of WC itself, the hardness of the composite ceramic tool material is increased and the fracture toughness is also significantly improved. When the WC addition amount is 30 vol.%, the fracture toughness of the composite ceramic tool material decreases slightly because excessive WC will make its grains larger, which Figures 1 to 3 It can also be seen.

[0077] The XRD patterns of the WC / β-SiAlON composite ceramic tool materials prepared in Examples 1 to 2 and Comparative Example 1 are shown in FIG. Figure 4 .

[0078] from Figure 4 It can be seen that there are only β-SiAlON and WC phases in the WC / β-SiAlON composite ceramic tool material, and no other phases.

[0079] Through analysis, it can be seen that the optimal addition amount of WC is 20 vol.%. At this time, the WC / β-SiAlON composite ceramics achieve improved electrical conductivity (low resistivity), hardness and fracture toughness, and fully prove that WC has a huge positive effect on β-SiAlON ceramics.

[0080] Example 3

[0081] The same as Example 1, except that the particle size of the WC powder used in step (2) is 0.6 μm.

[0082] The test results show that the WC / β-SiAlON composite ceramic tool material prepared in this embodiment has a resistivity of 1.57Ω·m, a Vickers hardness of 17.12±0.18GPa, and a fracture toughness of 6.97±0.12MPa·m. 1 / 2 .

[0083] Comparative Example 2

[0084] The same as Example 1, except that the particle size of the WC powder used in step (2) is 2 μm.

[0085] The test analysis shows that the resistivity of the WC / β-SiAlON composite ceramic tool material prepared in this comparative example is 1.95×10 7 Ω·m, Vickers hardness is 16.20±0.12GPa, fracture toughness is 6.83±0.19MPa·m 1 / 2 .

[0086] Comparative Example 3

[0087] The same as Example 1, except that only β-SiAlON ceramic powder is used for preparation.

[0088] The preparation method is specifically as follows:

[0089] (1) β-SiAlON ceramic powder, the raw materials include, by mass percentage, 84.18% of Si3N4 powder, 5.58% of Al2O3 powder, 2.24% of AlN powder and 8% of Sm2O3 powder.

[0090] Preparation of β-SiAlON ceramic powder: The raw materials were mixed in anhydrous ethanol according to mass percentage, subjected to ultrasonic oscillation (frequency of 40 kHz) and mechanical stirring for 2 hours, and then dried (dried at 120°C for 6 hours), ground and sieved (100 mesh) to obtain β-SiAlON ceramic powder. The solid solution parameter z value of β-SiAlON in the β-SiAlON ceramic powder was 0.5.

[0091] (2) β-SiAlON ceramic powder was poured into a graphite mold and then subjected to spark plasma sintering at a sintering pressure of 30 MPa. The powder was heated to 1700°C at a heating rate of 100°C / min and kept at that temperature for 10 min. Finally, the power was turned off and the powder was cooled. The sintered sample was demolded to obtain β-SiAlON ceramic tool material.

[0092] After testing and analysis, the resistivity of the β-SiAlON ceramic tool material prepared in this comparative example is 1.26×10 10 Ω·m, Vickers hardness is 16.46±0.29GPa, fracture toughness is 6.81±0.10MPa·m 1 / 2 .

[0093] Comparative Example 4

[0094] The same as Example 1, except that step (3) is specifically as follows: the raw materials and anhydrous ethanol are mixed in a mass ratio of 1:3 by volume, poured into a stainless steel tank, and ball milled using a high-energy planetary ball mill (speed of 250 r / min, ball milling time of 24 h, using Si3N4 balls), and then the obtained slurry is dried at 120°C for 6 h. Finally, the dried and ground powder is sieved with a 100-mesh sieve to obtain the WC / β-SiAlON composite ceramic raw powder.

[0095] The test results show that the WC / β-SiAlON composite ceramic tool material prepared in this comparative example has a resistivity of 0.43Ω·m, a Vickers hardness of 16.73±0.26GPa, and a fracture toughness of 6.96±0.15MPa·m. 1 / 2 .

[0096] Comparative Example 5

[0097] The same as Example 1, except that the WC powder in step (2) is replaced by an equal volume of Ti(C,N) powder (particle size of 0.06 μm).

[0098] The test results show that the resistivity of the Ti(C,N) / β-SiAlON composite ceramic tool material prepared in this comparative example is 2.24Ω·m, the Vickers hardness is 16.86±0.33GPa, and the fracture toughness is 6.87±0.21MPa·m. 1 / 2 .

[0099] By comparing Comparative Example 2 with Examples 1 and 3, it can be found that WC with a smaller particle size (0.06 μm) helps to improve the electrical and mechanical properties of β-SiAlON ceramics, while WC with a larger particle size (2 μm) has no obvious effect on promoting the conductivity of β-SiAlON ceramics and instead reduces their mechanical properties.

[0100] By comparing Comparative Example 3 with Example 1, it can be found that, compared with pure β-SiAlON ceramic material, adding an appropriate amount of WC can greatly improve the electrical and mechanical properties of β-SiAlON ceramics.

[0101] By comparing Comparative Example 4 with Example 1, it can be found that the mechanical properties of the WC / β-SiAlON composite ceramics obtained by the mixing process of ultrasound and mechanical stirring (Example 1) are better than those obtained by the ball milling process (Comparative Example 4), and the conductive properties of the WC / β-SiAlON composite ceramics obtained by the mixing process of ultrasound and mechanical stirring are comparable to those obtained by the ball milling process.

[0102] By comparing Comparative Example 5 with Example 1, it can be found that although Ti(C,N) also has good conductivity, it is not as effective as WC in improving the electrical conductivity and mechanical properties of β-SiAlON ceramics. This shows that the enhancement effect is not only related to the conductivity of the conductive phase itself, but also has a lot to do with the shape and structure of the conductive phase.

[0103] The embodiments described above are merely descriptions of preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Without departing from the spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by persons skilled in the art should fall within the scope of protection defined by the claims of the present invention.

Claims

1. A conductive WC / β-SiAlON composite ceramic tool material with high mechanical properties, characterized in that: In terms of volume percentage, the raw materials include: 70-80% of β-SiAlON ceramic powder and 20-30% of WC powder; The β-SiAlON ceramic powder comprises, by mass percentage, 84-85% Si3N4 powder, 5-6% Al2O3 powder, 2-3% AlN powder and 6-9% Sm2O3 powder; The preparation method of the β-SiAlON ceramic powder comprises the following steps: The raw materials are mixed in an organic solvent, subjected to ultrasonic oscillation and mechanical stirring, and then dried, ground and sieved to obtain the β-SiAlON ceramic powder; The particle size of the WC powder is 0.05 to 1 μm; The preparation method of the WC / β-SiAlON composite ceramic tool material comprises the following steps: The raw materials are added into an organic solvent, subjected to ultrasonic vibration and mechanical stirring, and then dried, ground and sieved to obtain WC / β-SiAlON composite ceramic raw powder; The WC / β-SiAlON composite ceramic raw powder is sintered to obtain the WC / β-SiAlON composite ceramic tool material; The sintering is spark plasma sintering; The process parameters of the spark plasma sintering include: a sintering pressure of 20 to 50 MPa, a sintering temperature of 1650 to 1750° C., and a heat preservation time of 5 to 15 minutes.

2. The WC / β-SiAlON composite ceramic tool material according to claim 1, characterized in that: When preparing WC / β-SiAlON composite ceramic tool material, the mass ratio of the raw material to the organic solvent is 1:(2-5); The frequency of the ultrasonic oscillation is 30-50 KHz; the time of the ultrasonic oscillation plus mechanical stirring is 0.5-3 hours.

3. The WC / β-SiAlON composite ceramic tool material according to claim 1, characterized in that: When preparing WC / β-SiAlON composite ceramic tool material, the mesh number of the sieving is 100-300 meshes.

4. Use of the WC / β-SiAlON composite ceramic tool material according to any one of claims 1 to 3 in the preparation of cutting tools.